Characteristics of the Savonius turbine to variation angles - Su'udy, Ahmad Hamim; Prasetiyo, Budhi; Aulia, Nur Fatowil; Surindra”¬, ”ªMochamad Denny; Safarudin”¬, ”ªYanuar Mahfudz; Sutanto, Bayu (Politeknik Negeri Semarang, 2023)
Wind energy is a form of energy that can be converted into electrical energy using a wind turbine. Based on the axis of rotation, wind turbines are of two types, namely horizontal axis wind turbines and vertical axis wind turbines. Wind turbines with a vertical axis have several types including Darrieus wind turbines, Savonius wind turbines, and H wind turbines. The purpose of this manufacture and test is to determine the effect of wind speed and system efficiency from the Savonius 8 blade wind turbine with variations in the angle of attack on wind speed. certain. Based on the test results, it can be seen that the highest generator power value is at a wind speed of 6 m/s worth 3.85 Watt with an angle of attack of 20 ° and a load of 1 DC lamp, a wind speed of 7 m/s worth 5.58 Watt with an angle of attack f 0 ° and a load 3 DC lamps, wind speed of 8 m/s worth 8,52 Watts with an angle of attack of 5 ° and a load of 4 DC lamps. While the highest system efficiency value is obtained at a wind speed of 6 m/s worth 4,62 % with an angle of attack of 20 ° and a load of 1 DC lamp, a wind speed of 7 m/s worth 4,218 % with an angle of attack of 0 ° and a load of 3 DC lamps, wind speed 8 m/s worth 4,31 % with an angle of 5 ° and a load of 4 DC lamps.